Modeling the Human Development Index of the West Nusa Tenggara Province using Panel Data Regression - Astuti, Alfira Mulya; Islamiyah, Pizatul; Choir, Achmad Syahrul; Setambah, Mohd Afifi Bahurudin (Universitas Muhammadiyah Mataram, 2025)
The human development index is the primary indicator used to measure the level of success of human development. It is important to study because the human development index can provide a more comprehensive picture of a region or country's progress in improving its people's quality of life and guide the government in designing more effective development policies, identifying social gaps, and directing efforts to improve the quality of life of society as a whole. This research aims to identify the most significant component of the HDI calculation through the application of standardized coefficients and to analyze the influence of the number of poor people on the human development index in West Nusa Tenggara (NTB) province during 2010-2023 period. This research is quantitative in essence. The independent variables were life expectancy at birth, expected years of schooling, mean years of schooling, adjusted per capita expenditure, and number of poor people. The individual observation units in this study were 10 districts/cities in the NTB province. Data were sourced from Badan Pusat Statistik (BPS) NTB Province and analyzed using the panel regression method. The results of model selection show that the Fixed Effect Model is the best model for modeling the human development index in NTB province. The adjusted per capita expenditure had the greatest impact on the human development index of NTB Province in 2010–2023. The expected years of schooling was the variable that contributed the least to the entire components of the HDI in NTB province. The number of poor people had a significant effect on the human development index of NTB province from 2010 to 2023.